Dawabit al-Tajdid Ru’yah Islamiyyah - Muhammad Hossainy Musa al-Ghazali (Universitas Darussalam Gontor, 2009)
The tajdid (renewal) which involves the meaning of the non-existence invention should have the guidelines based on Islamic Law. By these guidelines, there will be no space for destructing religion in the name of tajdid. Consequently, the discussion on tajdid guidelines is an Islamic matter, so that the confusion between the right and the wrong will be eliminated. Tajdid is neither a complete chaos nor a strong desire to remove all religion’s original form. Also, it does not mean to do a judgment to the efforts done by the early Muslim scholars and who came after them, but tajdid in Islam should be based on the guidance given by Allah in order to achieve the aim of being deputies and empowerment in this world. Thus, it should not exceed the area of rules which are semi definitive (al-ahkam al-zanniah) which is the area of conducting ijtihad. Finally, the guidelines of tajdid in Islam comprise the rational knowledgeable, moral and Islamic guidelines, by which, the tajdid will be prevented from the misuse.